Evaluation of propolis activity as sucrose-dependent and sucrose-independent Streptococcus mutans inhibitors to treat dental caries using an in silico approach - Muhammad Miftah Jauhar, Putri Hawa Syaifie, Adzani Gaisani Arda, Donny Ramadhan, Dwi Wahyu Nugroho, Nofa Mardia Ningsih Kaswati, Alfian Noviyanto,, Nurul Taufiqu Rochman, Etik Mardliyati (Journal of Applied Pharmaceutical Science, 2023)
Dental caries is an oral disease that still shows high prevalence in the world. Streptococcus mutans as the main caries-related bacterium uses some features to exhibit its role as a cariogenic bacterium. It majorly can be classified into dependent and independent sucrose proteins. One natural source gaining interest regarding its potential to inhibit S. mutans activity is propolis. However, research has attempted to evaluate the potential inhibitor from propolis to caries-related protein S. mutans through an in silico approach. Therefore, this research aims to evaluate the compounds in propolis that have a high activity to inhibit glucosyltransferase and antigen I/II using an in silico method. Among 93 compounds from propolis screening, diosmetin, cosmosiin, genistin, and 3′-methoxy-5′-hydroxyisoflavone-7-O-β-D glucoside showed as the best candidate. These potential ligands exhibited high docking stability with the conserved amino acid residue and low dynamics fluctuation. Therefore, this research can provide further insight into dental caries drug development.